Variation in the geometry of specimen under dynamic tensile loading - Ira Nursyilah Mohd Tahir (2015)
All materials used in our daily activities undergo loadings of various forms such as dynamic and impact type loading. As such it is vital to predict the response of materials to different dynamic loading conditions. Hence mechanical properties of materials such as ductility, elasticity, strength and hardness are studied upon in order to aid engineers in selecting the most suitable material for a specific design or purpose. Furthermore there are numerous applications where materials undergo extreme conditions that are characterized by high stress and high strain rates. Thus its structural integrity is also accessed upon to ensure that the material is safe to be used under high stress and strain rate loading. This project uses the Split Hopkinson Pressure Bar to achieve the required high train rates condition to study the mechanical behaviors of a material. The project aim to analyze the effects of variation in geometry of the specimen under dynamic tensile loading. The geometry of the Al6061-T6 specimens varies in gauge length width, where the length and shoulder radius are maintained unchanged. These specimen will be tested at insertion distance of 700mm and 5mm. Calibration test will be conducted first with Al6061-T6 of width 4mm to validate the reliability of the Split Hopkinson Pressure Bar. This is done by comparing calibration test result recorded in published journals. Tests on variation of width is then carried out to study the effects of varying specimen width of 3, 4 and 5mm on physical property of the material under dynamic loading at high strain rates. The stress-strain effect and strain rate experienced will be looked into during this experiment